Management of Performing Arts Sanggar Sarai Sarumpun in the Performing Arts Industry in the City Of Padang - Mustika, Rilla; Desfiarni (Universitas Negeri Padang, 2023)
This study aims to explain and describe the Performing Arts Management System at Sanggar Sarai Sarumpun in the Performing Arts Industry in Padang City. This type of research is qualitative research using a descriptive method. The research instrument is the author himself and is assisted by supporting instruments such as writing instruments and cameras. This type of data uses primary data and secondary data. Data collection techniques were carried out through library research, observation, interviews and documentation. Data analysis is done by collecting data, describing the data and concluding the data. From the results obtained, the management of the Sarai Sarumpun Studio has a plan by making programs that will be carried out and will be implemented, with the preparation of equipment and exercises. Organizing has been done by making a line-shaped management structure. Organizing also determines the duties and authorities of the board. Mobilization is done by carrying out the provision of motivation, and guidance and moving on to the set goals. Internal supervision is carried out directly or indirectly, then external supervision is carried out by evaluating activities. Sanggar Sarai Sarumpun also has a production house consisting of dances, music, night bainai, babako. Marketing management from Sarai Sarumpun also keeps up with the times. Sanggar Sarai Sarumpun has been registered with the Tourism Office and is collaborating with the agency. The management of the organization chosen by Sanggar Sarai Sarumpun shows democratic management.